The vulnerability factors to HIV transmission among long distance truck drivers working from Windhoek, Namibia - Majoni, Wilbert Kurauone (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.